Perancangan dan Pembuatan Sistem Perparkiran Kendaraan pada Gedung 2 Tingkat dengan Memanfaatkan RFID (Radio Frequency Identification) Berbasis Mikrokontroler ATMEGA328 - Microfindia, Egal (TSAQOFAH, 2026)
The design of this prototype was motivated by the need for an automatic vehicle parking system in a two-story building to facilitate the arrangement and management of parking, which is often disorganized. This study aims to design, develop, and implement an automatic vehicle parking system by utilizing RFID as the input, a servo motor as the output for opening the entrance gate barrier, an infrared sensor as the input for counting the number of users entering and exiting, Arduino Uno (ATmega 328 microcontroller) as the main controller, and an LCD as the information medium for the number of available parking spaces. The system design process was carried out using Arduino IDE software. The test results showed that the vehicle parking system in this two-story building could operate automatically, as indicated by the LCD display showing the remaining unoccupied parking capacity. When the parking capacity was full, the parking gate barrier could no longer be opened and the LCD displayed information that the parking area was full. These findings indicate that the designed system is capable of supporting more orderly and automatic parking management.